The Evolution of Da’awah in Multicultural and Pluralistic Societies in Gombe State - Abdullahi, Auwal (Civiliza Publishing, 2025)
This study examines the evolution of da’wah in Gombe State, Nigeria, a region characterized by ethnic diversity and religious pluralism where Islam, Christianity, and indigenous beliefs coexist. It explores the challenges and opportunities of propagating Islamic teachings within this multicultural setting. Using a descriptive-qualitative approach and literature review, the research analyzes historical, sociological, and thematic perspectives to understand how da’wah strategies have adapted from the pre-colonial period to the digital age. Findings show that while da’wah has historically relied on cultural adaptation and community engagement, modern challenges such as religious tension, extremist narratives, and globalization require innovative approaches. Inclusive methods—such as interfaith dialogue, intercultural communication, and integration of local traditions—have proven effective in promoting tolerance and peaceful coexistence. Digital platforms, particularly social media, offer significant opportunities to reach younger audiences, though they also pose risks of misinformation and radicalization. The study highlights the role of Islamic organizations, notably Jama’atu Nasril Islam, in balancing religious propagation with social services, education, and interfaith initiatives. It concludes that effective da’wah in pluralistic societies should emphasize wisdom (hikmah), dialogue (mujadalah), and cultural sensitivity, while leveraging technology and promoting universal values such as justice, compassion, and solidarity. Recommendations include training da’wah practitioners in digital literacy and intercultural skills, empowering women and youth in da’wah activities, and strengthening collaboration with government and non-Muslim stakeholders. Ultimately, the study underscores that da’wah must function not only as religious propagation but also as a catalyst for harmony, tolerance, and social justice in diverse societies.